Physiological Effects of Prolonged Internet Use on Heart Health Effect, Sleep Patterns, Appetite, and Musculoskeletal Health - Saly Naser Abbas (Kerbala Journal of Nursing and Health Sciences., 2026)
Introduction: The paper examined the effects of the extended use of the internet on cardiovascular symptoms, sleeping habits, appetite, and musculoskeletal wellbeing. The survey was a cross-sectional survey of 185 adult subjects, which measured daily screen time and pre-sleep exposure, sleep quality, physical complaints, changes in appetite, and cognitive symptoms. The results showed that widespread long-term internet usage, exposure to it just before going to bed, insomnia, low sleep quality, and morning fatigue were common. The complaints that were regularly mentioned were fatigue, palpitations, appetite disregulation, neck, shoulder, and back pain. Additionally, there was a great effect on the heart rate of the participants, and many of them claimed that their resting heart rate was high and they experienced tachycardia occasionally, which was likely due to the enhanced sympathetic activity. To conclude, the idea of chronic internet use appears to be a major behavioral stress factor in need of the implementation of healthier digital habits and additional longitudinal research. Methods: Our research design was A cross-sectional quantitative survey, which entailed 185 adult internet users to investigate the effects of a long-term internet use on physiological and behavioral consequences. The respondents completed a questionnaire, which contained questions on their daily internet use, exposure to screens before sleep, cardiovascular responses to online actions, sleeping disturbances, appetite alterations, musculoskeletal symptoms, and cognitive symptoms, including eyestrain and loss of concentration. The analysis of the data was performed by the descriptive statistics that covered frequencies and percentages and were presented in the tables and in Figure. The method helped to determine the common trends of internet use over a long period of time and its association with autonomic, musculoskeletal and neurocognitive outcomes. Results: The findings part includes the distribution of the responses of the participants in the case of daily internet. Use, sleep patterns, behaviors about the appetite, and musculoskeletal symptoms. Findings are recorded in frequencies and percentages and presented in the form of graphical figures. Conclusion According to this study, there are physiological, behavioral, and cognitive effects of the effects of long internet use. Excessive use can disrupt sleep causing difficulty in falling asleep, staying asleep, morning drowsiness and circadian rhythm disturbance. The alterations in eating habits might cause metabolism problems, whereas cognitive and neurological stress would cause headaches, stress, and overload especially during disconnections or interruptions. The effects vary depending on personal usage patterns, lifestyle and physiological strength. These findings represent the relevance of both deliberate and moderate internet use in duration and timing. Additional longitudinal studies are encouraged in order to study causal correlations and preventive measures.